1 Changing paradigm in graduate education: Collaborative On-line Approach in Reproduction. (7th December 2018) - Parrish, J; Keating, A; Pate, J; Pohler, K; Wiltbank, M; Ealy, A
Abstract: Reduction in faculty and graduate student numbers at Land-Grant Universities necessitate revisiting the graduate education model. A multi-institutional online approach was organized by NE1727 to address this problem in Animal Sciences with Reproductive Physiology as the model. Six instructors and 31 students from 5 universities participated in Advanced Reproduction, 3 credits, with registration at each student's home institution. The learning objectives were to compare and contrast various reproductive processes; investigate new and emerging reproductive technologies; and interpret primary literature. To accomplish the learning objectives, students viewed prerecorded lectures and instructors led a 2-hr live discussion of assigned published manuscripts in the weekly topic area. Lectures and manuscripts were made available to students via a cloud-based Google Drive. The discussion was conducted live using Zoom video conferencing software (San Jose, CA). A subset of students was assigned as designated reviewers of weekly manuscripts, required to submit a written review prior to class, and had lead roles during the discussion. A peer evaluation of written reviews was conducted in the following week. A final written assignment on an agreed-upon topic was required at the end of the semester. Written assignments were reviewed by the weekly instructor in charge but the final assignment, participation grade and final grade were assigned by the home institution instructor. Student evaluation comments indicated beneficial aspects were prerecorded lectures, a mix of content-based lecture with a journal club style, written reviews, and within-institution conversations after the teleconference. Negative aspects were the 2-hr discussion length without a break and peer review writing assignments that didn't achieve objectives. On-line course design needs to address funding model, learning management systems, video conferencing software, Google Drive access, ensuring lectures are viewed in advance, and student adaption to different instructor expectations.